Design of 3-DOF Force Sensing Micro-Forceps for Robot Assisted Vitreoretinal Surgery() - Gonenc, Berk (2013)
Vitreoretinal surgery is associated with serious complications that can easily stem from excessive tissue manipulation forces while the forces required for such surgery are routinely well below human tactile sensation. Despite the critical need in this area, there is still no practical vitreoretinal instrument that can sense both the axial and transverse tool-to-tissue interaction forces with sub-mN accuracy. In this study, we present the conceptual design and optimization of a 3 degrees-of-freedom (DOF) force sensing micro-forceps as the next generation of our force sensing instruments. 4 fiber Bragg grating (FBG) strain sensors are integrated in the design to measure tool tip forces.